PENERAPAN SMART ENVIRONMENT PADA PROGRAM KAMPUNG IKLI DI KAMPUNG RANDAKARI KECAMATAN CIWANDAN DALAM MEWUJUDKAN KOTA CILEGON SEBAGAI SMART CITY - Wahyuningsih, Putri; Nurimani, Nissa; Prasetyo, Eko (Jurnal Ilmiah Wahana Pendidikan, 2024)
The fast improvement of Data and Correspondence Innovation (ICT has rolled out an improvement or sped up potential chances to change a condition into an “clever” counterfeit climate, which is associated through sensors and mechanized contraptions. Cilegon city already has a plan to become a smart city through Mayor Regulation Number 106 of 2016 regarding the implementation of electronic-based government systems. The motivation behind this study is to settle on the utilization of a shrewd climate in an ecologically solid city program in Randakari City, Cilegon Territorial Government in acknowledging Cilegon City as a Brilliant City. The problem that is the focus of this research is How to Implement Smart Environment through the Climate Village Program in Randakari Village, Ciwandan District in Realizing Cilegon City as a Smart City. This study employs a qualitative approach by choosing case study research as the type of research. The Randakari Village PROKLIM program is carried out by RW 01 through the operation of a waste bank, empowerment houses, and sustainable food houses.